2016
DOI: 10.1111/cen.13052
|View full text |Cite
|
Sign up to set email alerts
|

Liothyronine use in a 17 year observational population‐based study ‐ the tears study

Abstract: For patients taking long-term liothyronine we did not identify any additional risk of atrial fibrillation, cardiovascular disease or fractures. There was an increased incident use of antipsychotic medication during follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 36 publications
(92 reference statements)
0
56
1
Order By: Relevance
“…Differences in GHQ caseness and HADS anxiety were not apparent after 12 months. A recent pharmacoepidemiological study did not identify any additional risk of atrial fibrillation, cardiovascular disease or fractures with liothyronine [20].…”
Section: Review Of Existing Evidencementioning
confidence: 89%
“…Differences in GHQ caseness and HADS anxiety were not apparent after 12 months. A recent pharmacoepidemiological study did not identify any additional risk of atrial fibrillation, cardiovascular disease or fractures with liothyronine [20].…”
Section: Review Of Existing Evidencementioning
confidence: 89%
“…67 The only difference that reached statistical significance was an increase in the new use of antipsychotic drugs, an effect that was associated with the use of LT3 (adjusted hazard ratio, 2.26 [95% CI, 1.64-3.11]; P < .01). 67 These data suggest that long-term treatment with LT3 is generally safe although the preponderance of longterm experience in the treatment of hypothyroidism involves LT4…”
Section: Other Considerations For Lt4/lt3 Combination Therapymentioning
confidence: 96%
“…The results were derived from relatively short‐term trials, with the longest study extending 1 year . A large, long‐term observational study with a maximum 17‐year follow‐up evaluated morbidity and mortality in patients treated with LT3 (n = 400; 327 patients received the LT3 with LT4, and 73 patients received LT3 alone) or LT4 alone (n = 33 955) . No statistically significant between‐treatment differences were observed in the incidences of death, cardiovascular disease, atrial fibrillation, diabetes or fracture outcomes .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been concerns regarding safety of long term LT3 use mainly due to lack of data. Leese et al [20] reported a 17yrs large observation population based study of all patients prescribed thyroid hormone replacement in Tayside Scotland from 1997 to 2014. LT3 was prescribed to 400 patient compared to 33,955 patients who were treated with LT4 monotherapy.…”
Section: Editorialmentioning
confidence: 99%